2018
DOI: 10.1186/s12958-018-0351-0
|View full text |Cite
|
Sign up to set email alerts
|

The monocyte counts to HDL cholesterol ratio in obese and lean patients with polycystic ovary syndrome

Abstract: BackgroundWomen with polycystic ovary syndrome are more likely to suffer from obesity, insulin resistance, and chronic low-grade inflammation. In fact, the excessive activation of monocytes exacerbates oxidative stress and inflammation. However, high-density lipoprotein cholesterol neutralizes the pro-inflammatory and pro-oxidant effects of monocytes. The aim of this study is to investigate whether monocyte counts to high-density lipoprotein cholesterol ratio can predict the inflammatory condition in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
1
56
1
3
Order By: Relevance
“…These data suggest that PCOS exacerbates obesity-dependent ovarian inflammation and oxidative stress (Ressler et al 2015). Distinct metabolic differences between obesity and PCOS include hyperandrogenemia, that is, obese women without PCOS have circulating total testosterone concentrations similar to lean control women (Keskin Kurt et al 2014, Alshammari et al 2017, Usta et al 2018. Other hormones increased in obese PCOS patients compared to obese women include insulin/glucose, LH andE2 (Keskin Kurt et al 2014, Usta et al 2018).…”
Section: Metabolic and Ovarian Phenotypes Of Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that PCOS exacerbates obesity-dependent ovarian inflammation and oxidative stress (Ressler et al 2015). Distinct metabolic differences between obesity and PCOS include hyperandrogenemia, that is, obese women without PCOS have circulating total testosterone concentrations similar to lean control women (Keskin Kurt et al 2014, Alshammari et al 2017, Usta et al 2018. Other hormones increased in obese PCOS patients compared to obese women include insulin/glucose, LH andE2 (Keskin Kurt et al 2014, Usta et al 2018).…”
Section: Metabolic and Ovarian Phenotypes Of Pcosmentioning
confidence: 99%
“…Based on these data, it is clear that obese women with PCOS have similar inflammatory and oxidative stress phenotypes to obese women. It should also be noted that there are PCOS women who have a normal BMI (Alshammari et al 2017, Li et al 2017, Usta et al 2018. Therefore, there are obese women without PCOS and lean women with PCOS.…”
Section: Metabolic and Ovarian Phenotypes Of Pcosmentioning
confidence: 99%
“…Anti-inflammatory effect of MHR depends on the pro-inflammatory and pro-oxidative effects of monocytes and the anti-inflammatory effect of HDL especially on endovascular system. 17,18 Kanbay et al 13 reported that MHR is an independent predictor factor for cardiovascular events in patients with chronic renal disease and that it is associated with decreased glomerular infiltration ratio. It has also been reported that in patients with Behçet's disease, MHR is associated with flow-mediated dilatation of brachial artery.…”
Section: Ta B L E 1 Distribution Of Patient and Control Groups By Gendermentioning
confidence: 99%
“…Recently, leukocytes' subtypes have been considered useful systemic inflammation markers [6] as well as neutrophil-to-lymphocyte ratio (NLR) [7,8], platelet-to-lymphocyte ratio (PLR) [9,10], lymphocyte-to-monocyte ratio (LMR) [11,12]and monocyte-to-HDL ratio (MHR) [13][14][15][16][17][18] indexes. Furthermore, several studies underlined the link between NLR, PLR, LMR, MHR and cardiovascular diseases, like peripheral arterial occlusive disease, coronary artery diseases (including myocardial infarction), atrial fibrillation and aortic alterations but the association with MS is still not well established [12,16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%